Using naturalistic driving data to better understand the driving exposure and patterns of older drivers. (28th February 2018) - Molnar, Lisa J.; Eby, David W.; Bogard, Scott E.; LeBlanc, David J.; Zakrajsek, Jennifer S.
ABSTRACT: Objective : The aging of the population in the United States and elsewhere has brought increasing attention to the issue of safe driving and mobility among older adults. The overall objective of this research was to use naturalistic data collection to better understand driving exposure and driving patterns, 2 important contributors to crash risk. Methods : Data came from a study conducted at the University of Michigan Transportation Research Institute as part of the Integrated Vehicle-Based Safety System (IVBSS) program. A total of 108 randomly sampled drivers took part, with the sample stratified by age and sex. The age groups examined were 20 to 30 (younger), 40 to 50 (middle-aged), and 60 to 70 years old (older). Sixteen late-model Honda Accords were used as research vehicles and were driven by participants as their personal vehicles over the study period. Roughly the first 2 weeks of vehicle use comprised the baseline driving period, during which the IVBSS technologies were turned off (i.e., no warnings were presented to the drivers) but all onboard data were collected. For this article, only data from the baseline period were analyzed to limit any confounding effects that the safety technology may have had on driving behavior. Results : Results indicated that when looking at age independent of sex, older drivers (age 60–70) took fewer trips, drove fewer minutes, were less likely to drive at night, and had fewer high decelerations and speeding events than the youngest age group (20–30). They were also less likely to drive during peak morning traffic and on high-speed roads than their middle-age counterparts (40–50). Across all age groups, there were few differences by sex, with the exception that females drove fewer miles and fewer minutes and had fewer high decelerations than males. When both age and sex were taken into account, it was often the group of females age 60–70 that appeared to account for many of the age and sex differences found in driving exposure and patterns. Conclusions : Future research in this area would benefit from larger scale and longitudinal study designs so that changes in driving exposure and patterns over time among large samples of drivers could be examined.